Fundamentals of microbiology - Pommerville, Jeffrey C. (Burlington, Massachusetts : Jones & Bartlett Learning, 2022)
"Fundamentals of Microbiology is the flagship title of the JBL Science list. It is designed for the introductory microbiology course with an emphasis in the health sciences. As such, the textbook is used primarily for health care students in the fields of nursing, dental hygiene, medical assistance, and more, however it is also applicable to students in the areas of food science, biological science, and other health professions"--
Introduction to Microbiology : Then and Now -- The Chemical Building Blocks of Life -- Naming, Observing, and Cataloging the Microbial World -- Structure and Organization of Prokaryotic Cells -- Structure and Organization of Eukaryotic Microbial Cells and Parasites -- The Viruses and Other Infectious Agents -- Microbial Growth and Nutrition -- Microbial Metabolism -- Microbial Genetics -- Gene Transfer, Genetic Engineering, and Genomics -- Control of Microorganisms : Physical Methods and Chemical Agents -- Control of Microorganisms : Antimicrobial Drugs and Superbugs -- Diagnosing Infections -- Infectious Diseases of the Respiratory System -- Infectious Diseases of the Digestive System -- Infectious Diseases Affecting the Skin, Soft Tissues, and Eyes -- Infectious Diseases of the Nervous System -- Systemic Infectious Diseases -- Infectious Diseases of the Urinary and Reproductive Systems -- The Host-Microbe Relationship and Infectious Disease Epidemiology -- The Immune Response to Infection : Innate Immunity -- Resistance and the Immune System : Adaptive Immunity -- Infectious Disease and Immune Disorders.
Includes index.
Keywords: Microbiological Phenomena